The WIPI Gene Family and Neurodegenerative Diseases: Insights From Yeast and Dictyostelium Models - Vincent, Olivier; Antón-Esteban, Laura; Bueno-Arribas, Miranda; Tornero-Écija, Alba; Navas, María-Ángeles; Escalante, Ricardo (Frontiers in Cell and Developmental Biology, 2021)
WIPIs are a conserved family of proteins with a characteristic 7-bladedβ-propeller structure. They play a prominent role in autophagy, but also in other membrane trafficking processes. Mutations in human WIPI4 cause several neurodegenerative diseases. One of them is BPAN, a rare disease characterized by developmental delay, motor disorders, and seizures. Autophagy dysfunction is thought to play an important role in this disease but the precise pathological consequences of the mutations are not well established. The use of simple models such as the yeast Saccharomyces cerevisiae and the social amoeba Dictyostelium discoideum provides valuable information on the molecular and cellular function of these proteins, but also sheds light on possible pathways that may be relevant in the search for potential therapies. Here, we review the function of WIPIs as well as disease-causing mutations with a special focus on the information provided by these simple models.